Genetics and muscle pathology in the diagnosis of muscular dystrophies: An update - Deepti Narasimhaiah; Megha S Uppin; Prajnya Ranganath (Wolters Kluwer Medknow Publications, 2022)
Muscular dystrophies are a clinically and genetically heterogeneous group of disorders involving the skeletal muscles. They have a progressive clinical course and are characterized by muscle fiber degeneration. Congenital muscular dystrophies (CMD) include dystroglycanopathies, merosin-deficient CMD, collagen VI-deficient CMD, SELENON-related rigid spine muscular dystrophy, and LMNA-related CMD. Childhood and adult-onset muscular dystrophies include dystrophinopathies, limb-girdle muscular dystrophies, Emery-Dreifuss muscular dystrophy, facioscapulohumeral muscular dystrophy, and myotonic dystrophy. Traditionally, muscle biopsy and histopathology along with special pathology techniques such as immunohistochemistry or immunoblotting were used for the diagnosis of muscular dystrophies. However, recent advances in molecular genetic testing, especially the next-generation sequencing technology, have revolutionized the diagnosis of muscular dystrophies. Identification of the underlying genetic basis helps in appropriate management and prognostication of the affected individual and genetic counseling of the family. In addition, identification of the exact disease-causing mutations is necessary for accurate prenatal genetic testing and carrier testing, to prevent recurrence in the family. Mutation identification is also essential for initiating mutation-specific therapies (which have been developed recently, especially for Duchenne muscular dystrophy) and for enrolment of patients into ongoing therapeutic clinical trials. The 'genetic testing first' approach has now become the norm in most centers. Nonetheless, muscle biopsy-based testing still has an important role to play, especially for cases where genetic testing is negative or inconclusive for the etiology.